BIMBINGAN DAN PELATIHAN PENYIMPANAN ARSIP PESERTA DIDIK SECARA ELEKTRONIK - Tatiana Kristianingsih; Becik Gati Anjari; Rizka Rahmawati; Erlangga Andi Sukma; Titien Indrianti (P3M Politeknik Negeri Malang, 2023)
School administration is one of the important things in the administration of education. With so many administrative activities, effective and efficient management is needed. The application of electronic archives has the main advantage which lies in the ease of management and management of records. Given the importance of managing electronic records, this guidance and training will be provided to teachers of Kindergarten ABA 38 Malang, because the school is a new school and is currently carrying out accreditation. In this activity the PPM team conducted counseling, discussions, mentoring and evaluation. After carrying out the education, further discussions were held regarding the case studies that would be raised in the mentoring and selected filings for school accreditation. So that assistance is focused on structuring evidence of school accreditation which consists of 8 standards, namely developmental achievements, content standards, process standards, educators and teaching staff, infrastructure, management standards, cost standards, assessment standards. After the training and mentoring the partners were very satisfied because it was very helpful to manage their school archives. In addition, partners feel more prepared for accreditation because the evidence prepared is tidier and easier to find.